Method for reducing oxygen content of sintered neodymium-iron-boron magnet and neodymium-iron-boron magnet
By adding rare earth NdFeB ultrafine powder to easily oxidize green bodies for companion sintering, the problem of NdFeB magnets being easily oxidized during sintering, the magnetic performance and product stability are improved.
Patent Information
- Application Number
- CN202311247048.8
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-09-25
- Publication Date
- 2025-03-25
AI Technical Summary
In the prior art, neodymium iron boron magnets are easily oxidized during the sintering process, resulting in reduced magnetic properties and insufficient product stability.
During the sintering of the green neodymium iron boron magnet, the easily oxidized green neodymium containing rare earth neodymium iron boron ultrafine powder, is added for companion sintering, and the high activity of the ultrafine powder absorbs oxygen in the sintering furnace to reduce the oxygen content in the magnet.
It effectively reduces the oxygen content of neodymium iron boron magnets, improves magnetic properties and product stability, and at the same time, it is simple in process and has low requirements for equipment.
Smart Images

Figure CN119694762A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of rare earth NdFeB permanent magnet materials, and in particular to a method for reducing the oxygen content of a sintered NdFeB magnet and the NdFeB magnet. Background Art
[0002] NdFeB is an important rare earth permanent magnet material with high magnetic energy product, high coercivity, light weight and low cost. It is the most cost-effective magnet so far and is known as the "King of Magnets". It is widely used in electronics, automobiles, computers, energy, medical equipment and many other fields.
[0003] Since rare earth elements are highly active and easily oxidized, when the oxygen content of sintered magnets is too high, on the one hand, their comprehensive magnetic properties will be reduced due to the addition of non-magnetic oxygen. On the other hand, these oxygen atoms will easily form crack initiation points after entering the interior of the magnet, seriously affecting its use in harsh service environments. Controlling oxygen content and reducing product oxidation are important key points in the production process.
[0004] At present, the commonly used method is to add a very small amount of antioxidant after hydrogen crushing and before jet milling or after jet milling, and coat the surface of magnetic powder with antioxidant by physical mixing to prevent oxidation of magnetic powder in contact with oxygen and water vapor in the air, reduce the oxygen content of sintered NdFeB magnets, and thus improve the magnetic properties of sintered NdFeB magnets. Antioxidants are mainly added in the magnetic powder stage before sintering products. During the sintering process, the additives will be decomposed by heat at 400℃ and discharged from the product. In the subsequent sintering process, the oxidation of rare earth in the product cannot be prevented. Therefore, the sintered NdFeB magnets still have a high oxygen content.
[0005] The patent application with publication number CN 111554499 A provides a method for reducing the oxygen content of sintered NdFeB permanent magnets. The method performs a hot pressing densification process on the blank after orientation forming, thereby increasing the density of the pre-sintered blank, reducing the pores in the blank, and discharging most of the impurity gases in the sintering process, thereby ultimately reducing the oxygen content of the sintered NdFeB permanent magnets. The method requires hot pressing before sintering the product, which increases the operation process in production and reduces production efficiency.
[0006] In summary, the prior art still lacks a simple and effective technical solution to the oxidation problem of NdFeB magnets during the sintering process. Summary of the invention
[0007] The main purpose of the present invention is to provide a method for reducing the oxygen content of a sintered NdFeB magnet and a NdFeB magnet, so as to solve the problem in the prior art that the NdFeB magnet is easily oxidized during the sintering process.
[0008] In order to achieve the above object, according to one aspect of the present invention, a method for reducing the oxygen content of sintered NdFeB magnets is provided, the method comprising: when the NdFeB magnet green body is sintered, an easily oxidizable green body containing rare earth NdFeB ultrafine powder is placed in the sintering environment for co-firing.
[0009] Furthermore, the particle size D50 of the rare earth NdFeB ultrafine powder is less than 1.5 μm.
[0010] Further, the rare earth NdFeB ultrafine powder is collected during the jet milling process;
[0011] Preferably, the total amount of rare earth in the rare earth NdFeB ultrafine powder is ≥50wt%.
[0012] Furthermore, the easily oxidizable green body contains 1 wt‰ to 5 wt‰ of antioxidant and 1 wt‰ to 5 wt‰ of lubricant.
[0013] Furthermore, the easily oxidizable green body is prepared by the following preparation method: rare earth neodymium iron boron ultrafine powder, antioxidant and lubricant are mixed, and pressed into a shape to obtain an easily oxidizable green body.
[0014] Furthermore, the mixing is carried out in a mixer, and the mixing time is 60 to 90 minutes.
[0015] Furthermore, the press molding is performed in an environment where the oxygen content is lower than 20 ppm.
[0016] Furthermore, during sintering, the volume ratio of the easily oxidizable green body to the NdFeB magnet green body in the same sintering environment is 1:9 to 2:3.
[0017] Furthermore, during sintering, the easily oxidizable green compacts are placed in a dispersed manner; preferably, the easily oxidizable green compacts are placed at the edge of the sintering environment, and / or the easily oxidizable green compacts are placed at intervals from the NdFeB magnet green compacts.
[0018] According to another aspect of the present invention, there is provided a NdFeB magnet, which is prepared by any one of the above methods for reducing the oxygen content of a sintered NdFeB magnet.
[0019] The technical solution of the present invention is applied, and an easily oxidizable green body containing rare earth NdFeB ultrafine powder is added to the sintering process of the NdFeB magnet green body for co-firing. Since the rare earth NdFeB ultrafine powder has fine particle size, high activity, and is very easy to oxidize, it can absorb and consume oxygen in the sintering furnace, thereby reducing the oxidation of normal products, thereby reducing the oxidation of the product NdFeB magnet during sintering, reducing the oxygen content in the magnet, and thus improving the magnetic properties of the sintered NdFeB magnet. The method can effectively reduce the oxygen content in the blank and increase the stability of producing high-performance products. In addition, the method has a simple process and low equipment requirements. BRIEF DESCRIPTION OF THE DRAWINGS
[0020] The drawings constituting a part of the present application are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute an improper limitation of the present invention. In the drawings:
[0021] Figure 1 A schematic diagram showing the arrangement of the ultrafine powder green body and the NdFeB magnet product green body according to Example 1 of the present invention is shown;
[0022] Figure 2 A schematic diagram showing the arrangement of the ultrafine powder green body and the NdFeB magnet product green body according to Example 2 of the present invention is shown;
[0023] Figure 3 A schematic diagram showing the arrangement of the ultrafine powder green body and the NdFeB magnet product green body according to Example 3 of the present invention is shown;
[0024] Figure 4 A schematic diagram showing the arrangement of the ultrafine powder green body and the NdFeB magnet product green body according to Example 4 of the present invention is shown.
[0025] Among them, the above drawings include the following figure marks: 100, ultrafine powder green body; 200, NdFeB magnet product green body. DETAILED DESCRIPTION
[0026] It should be noted that, in the absence of conflict, the embodiments and features in the embodiments of the present application can be combined with each other. The present invention will be described in detail below with reference to the accompanying drawings and in combination with the embodiments.
[0027] As analyzed in the background technology of the present application, there is a problem in the prior art that NdFeB magnets are easily oxidized during the sintering process. In order to solve this problem, the present application provides a method for reducing the oxygen content of sintered NdFeB magnets and a NdFeB magnet.
[0028] According to a typical embodiment of the present application, a method for reducing the oxygen content of a sintered NdFeB magnet is provided, the method comprising: when the NdFeB magnet green body is sintered, an easily oxidizable green body containing rare earth NdFeB ultrafine powder is placed in the sintering environment for co-firing.
[0029] The present application adds an easily oxidizable green body containing rare earth NdFeB ultrafine powder to the sintering process of the NdFeB magnet green body for co-firing. Since the rare earth NdFeB ultrafine powder has fine particle size, high activity, and is very easy to oxidize, it can absorb and consume oxygen in the sintering furnace, thereby reducing the oxidation of normal products, thereby reducing the oxidation of the product NdFeB magnet during sintering, reducing the oxygen content in the magnet, and thus improving the magnetic properties of the sintered NdFeB magnet. This method can effectively reduce the oxygen content in the blank and increase the stability of producing high-performance products. In addition, the method has a simple process and low equipment requirements.
[0030] In order to further improve the oxygen absorption capacity of the easily oxidizable green body, the particle size D50 of the rare earth NdFeB ultrafine powder is preferably <1.5 μm.
[0031] In some typical embodiments of the present application, the rare earth NdFeB ultrafine powder is collected during the airflow milling process in the production process of NdFeB magnets, realizing the resource utilization of waste materials. Moreover, the ultrafine powder produced during the airflow milling process has a high rare earth content, wherein the total amount of rare earth is ≥50wt%, and the activity is very high, and it is very easy to oxidize. The green bodies made of these ultrafine powders are placed around normal products and will more easily absorb oxygen in the sintering furnace. Preferably, the rare earth NdFeB ultrafine powder produced during the above-mentioned airflow milling process is collected in a powder tank with an oxygen content of less than 20ppm after nitrogen exhaust, to prevent it from being over-oxidized before co-firing.
[0032] Since the rare earth NdFeB ultrafine powder is very active, in order to reduce the activity loss in the preparation process of easily oxidizable green bodies, and at the same time to improve the safety of the process of making easily oxidizable green bodies from rare earth NdFeB ultrafine powder and avoid dangerous conditions such as fire, in some embodiments of the present application, the above-mentioned easily oxidizable green bodies contain 1wt‰~5wt‰ of antioxidant and 1wt‰~5wt‰ of lubricant. At the same time, the addition of lubricant can improve the fluidity of the powder, facilitate the mixing of the above-mentioned ingredients and the implementation of the green body making process, and improve production efficiency.
[0033] The above antioxidant and lubricant can be selected from the prior art and there is no special requirement for this application.
[0034] Exemplarily, the antioxidant includes, but is not limited to, any one or more of polyethylene oxide alkyl ether, polyethylene oxide monofatty acid ester, and polyethylene oxide allyl ether.
[0035] By way of example, the lubricant includes, but is not limited to, any one or more of tetracarbyl alcohol, molybdenum disulfide, silicone oil, fatty acid amide, oleic acid, polyester, synthetic ester and carboxylic acid.
[0036] In some typical embodiments of the present application, the easily oxidizable green body is prepared by the following preparation method: ultrafine rare earth neodymium iron boron powder, an antioxidant and a lubricant are mixed and pressed to obtain an easily oxidizable green body.
[0037] In order to fully mix the antioxidant and the rare earth NdFeB ultrafine powder, namely the lubricant, in some embodiments of the present application, the mixing is carried out in a mixer for 60 to 90 minutes.
[0038] Preferably, the compression molding is carried out in an environment with an oxygen content of less than 20 ppm, which can effectively prevent the oxidation of the rare earth NdFeB ultrafine powder during the molding process, thereby improving its oxygen absorption capacity during the co-firing process.
[0039] There are no special requirements for the shape of the easily oxidizable green body obtained after press molding, which can be determined according to the process parameters of the press or the spatial structure of the sintering equipment.
[0040] In some embodiments of the present application, in order to facilitate the distinction from normal NdFeB magnet green bodies, the volume, size and shape of the easily oxidizable green bodies are different from those of normal NdFeB magnet green bodies. The specific size can be determined according to the shape and size of the pressing process or the sintering environment, and there are no special requirements.
[0041] When the above-mentioned easily oxidizable green compact is sintered together with the NdFeB magnet product green compact, the specific sintering conditions and parameter indicators can be specifically determined according to the requirements of the NdFeB magnet product. The method of the present application has no special requirements. In the existing sintering technology, the above-mentioned easily oxidizable green compact can be used for co-firing to achieve a good oxygen reduction effect.
[0042] In some embodiments of the present application, the sintering temperature is 1085-1095° C., and during stripping, the glove box is filled with nitrogen to exhaust oxygen until the oxygen content is less than 20 ppm.
[0043] In some embodiments of the present application, during sintering, the volume ratio of the easily oxidizable green body to the NdFeB magnet green body in the same sintering environment is 1:9 to 2:3, and the easily oxidizable green body has a good oxygen absorption effect, which can significantly reduce the oxygen content in the magnet, thereby improving the magnetic properties of the sintered NdFeB magnet. Exemplarily, the easily oxidizable green body accounts for 10%, 15%, 20%, 25%, 30%, 35%, 40% of the total volume of the green body in the graphite box, that is, the easily oxidizable green body and the NdFeB magnet green body, or any range between the two.
[0044] In order to further exert the oxygen absorption effect of the easily oxidizable green compacts, the easily oxidizable green compacts are dispersed during sintering; preferably, the easily oxidizable green compacts are placed at the edge of the sintering environment, and / or the easily oxidizable green compacts are spaced apart from the NdFeB magnet green compacts.
[0045] In some embodiments of the present application, after sintering is completed, the above-mentioned easily oxidizable green body is taken out, and the normal NdFeB magnet product is further subjected to heat preservation and failure treatment according to the existing process. This application has no special requirements and will not be introduced one by one here.
[0046] According to another typical embodiment of the present application, a NdFeB magnet is provided. The NdFeB magnet is prepared by any of the above methods for reducing the oxygen content of a sintered NdFeB magnet.
[0047] The NdFeB magnet is sintered by adding an easily oxidizable green body containing rare earth NdFeB ultrafine powder during the green body sintering process. Since the rare earth NdFeB ultrafine powder has fine particle size, high activity, and is very easy to oxidize, it can absorb and consume oxygen in the sintering furnace, thereby reducing the oxidation of normal products, thereby reducing the oxidation of the product NdFeB magnet during the sintering process, reducing the oxygen content in the magnet, and thus improving the magnetic properties of the sintered NdFeB magnet. This method can effectively reduce the oxygen content in the blank and increase the stability of producing high-performance products. In addition, the method has a simple process and low equipment requirements.
[0048] The beneficial effects of the present application will be further illustrated below in combination with embodiments and comparative examples.
[0049] Example 1
[0050] The 35UH powder is pressed and then isostatically pressed at 220 MPa to obtain a Φ20×30 NdFeB magnet 35UH green product.
[0051] The ultrafine powder (D50 is about 1 μm) produced during the air flow milling process is collected in a powder tank with an oxygen content below 20 ppm after nitrogen deoxygenation under nitrogen protection, and then 5‰ of antioxidant (Tianjin Yuesheng New Materials Research Institute NdFeB special antioxidant 1#) and 5‰ of lubricant (Tianjin Yuesheng New Materials Research Institute NdFeB special lubricant 6#) are added. The mixture is mixed in a mixer for 90 minutes and pressed in a press with an oxygen content below 20 ppm. The size of the molded ultrafine powder green body 100 is Φ30×30.
[0052] The pressed ultrafine powder green body 100 and the NdFeB magnet product green body 200 are placed in a graphite box. Figure 1 As shown in the figure (the figure mainly shows the placement position, not the proportional relationship, the same below), the ultrafine powder green body 100 is placed around the NdFeB magnet product green body 200. Among them, the ultrafine powder green body 100 accounts for 10% of the total volume of the green body in the graphite box. Then, it is sintered at 1085℃ for 7 hours in a vacuum sintering furnace.
[0053] After sintering, the sintered ultrafine powder green body 100 is taken out, and the sintered NdFeB magnet product green body 200 is kept at 900° C. for 4 hours, and then subjected to aging treatment at 460° C. for 4 hours to obtain a NdFeB magnet.
[0054] Example 2
[0055] The 35UH powder is pressed and then isostatically pressed at 220 MPa to obtain a 85*63*35 NdFeB magnet 35UH green product.
[0056] The ultrafine powder (D50 is about 1 μm) produced in the process of air flow milling is collected in a powder tank with oxygen content below 20 ppm after nitrogen deoxygenation under nitrogen protection, and then 5‰ antioxidant (Tianjin Yuesheng New Materials Research Institute NdFeB special antioxidant 1#) and 5‰ lubricant (Tianjin Yuesheng New Materials Research Institute NdFeB special lubricant 6#) are added. The mixture is mixed in a mixer for 90 minutes and pressed in a press with an oxygen content below 20 ppm. The size of the molded ultrafine powder green body is 75*60*35.
[0057] The pressed ultrafine powder green body 100 and the NdFeB magnet product green body 200 are placed in a graphite box. Figure 2 As shown, the ultrafine powder green body 100 is placed at the four corners, wherein the ultrafine powder green body 100 occupies 20% of the total volume of the green body in the graphite box. Then, it is sintered at 1085° C. for 7 hours in a vacuum sintering furnace.
[0058] After sintering, the sintered ultrafine powder green body 100 is taken out, and the sintered NdFeB magnet product green body 200 is kept at 900° C. for 4 hours, and then subjected to aging treatment at 460° C. for 4 hours to obtain a NdFeB magnet.
[0059] Example 3
[0060] The 35UH powder is pressed and then isostatically pressed at 220 MPa to obtain a 85*63*35 NdFeB magnet 35UH green product.
[0061] The ultrafine powder (D50 is about 1 μm) produced in the process of air flow milling is collected in a powder tank with oxygen content below 20 ppm after nitrogen deoxygenation under nitrogen protection, and then 5‰ antioxidant (Tianjin Yuesheng New Materials Research Institute NdFeB special antioxidant 1#) and 5‰ lubricant (Tianjin Yuesheng New Materials Research Institute NdFeB special lubricant 6#) are added. The mixture is mixed in a mixer for 90 minutes and pressed in a press with an oxygen content below 20 ppm. The size of the molded ultrafine powder green body is 75*60*35.
[0062] The pressed ultrafine powder green body 100 and the NdFeB magnet product green body 200 are placed in a graphite box. Figure 3 As shown, the ultrafine powder green body 100 is placed at the four corners and the middle position, wherein the ultrafine powder green body 100 occupies 30% of the total volume of the green body in the graphite box, and then sintered at 1085° C. for 7 hours in a vacuum sintering furnace.
[0063] After sintering, the sintered ultrafine powder green body 100 is taken out, and the sintered NdFeB magnet product green body 200 is kept at 900° C. for 4 hours, and then subjected to aging treatment at 460° C. for 4 hours to obtain a NdFeB magnet.
[0064] Example 4
[0065] The 35UH powder is pressed and then isostatically pressed at 220 MPa to obtain a 85*63*35 NdFeB magnet 35UH green product.
[0066] The ultrafine powder (D50 is about 1 μm) produced during the air flow milling process is collected in a powder tank with an oxygen content below 20 ppm after nitrogen deoxygenation. Then, 5‰ of antioxidant (Tianjin Yuesheng New Materials Research Institute NdFeB special antioxidant 1#) and 5‰ of lubricant (Tianjin Yuesheng New Materials Research Institute NdFeB special lubricant 6#) are added, mixed in a mixer for 90 minutes, and pressed in a press with an oxygen content below 20 ppm. The size of the molded ultrafine powder green body is Φ30×30.
[0067] The pressed ultrafine powder green body 100 and the NdFeB magnet product green body 200 are placed in a graphite box. Figure 4 As shown, the ultrafine powder green body 100 is arranged vertically and horizontally in the middle, wherein the ultrafine powder green body 100 occupies 40% of the total volume of the green body in the graphite box, and then sintered in a vacuum sintering furnace at 1085° C. for 7 hours.
[0068] After sintering, the sintered ultrafine powder green body 100 is taken out, and the sintered NdFeB magnet product green body 200 is kept at 900° C. for 4 hours, and then subjected to aging treatment at 460° C. for 4 hours to obtain a NdFeB magnet.
[0069] Example 5
[0070] The difference from Example 1 is that the ultrafine powder green body 100 accounts for 5% of the total volume of the green body in the graphite box.
[0071] Comparative Example 1
[0072] The same 35UH powder as in the example was used to perform compression molding and isostatic pressing in the same manner as in Example 1, and the green body after molding was placed in a graphite box without adding ultrafine powder green body. Then, it was sintered at 1085°C for 7 hours in a vacuum sintering furnace, kept at 900°C for 4 hours, and then aged at 460°C for 4 hours to obtain a NdFeB magnet.
[0073] The NdFeB magnets prepared in the above examples and comparative examples were tested for oxygen content and performance. The test results are shown in Table 1 below.
[0074] Among them, the remanence, intrinsic coercivity and maximum magnetic energy product are tested according to GB / T 24270-2009; the oxygen content is tested with an oxygen, nitrogen and hydrogen analyzer.
[0075] Table 1
[0076]
[0077]
[0078] By comparing the oxygen content and performance test results of the above embodiment and the comparative example, it can be seen that the oxygen content of the product blank is significantly reduced by sintering the superfine powder with the normal product using the present invention, and the obtained product performance is qualified, which helps to improve the product performance and increase the stability of product production. At the same time, the operation process of the present invention is simple and has low requirements on equipment. The method for reducing the oxygen content of sintered NdFeB magnets has great practical value.
[0079] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for reducing the oxygen content of sintered NdFeB magnets, characterized in that: include: When the NdFeB magnet green body is sintered, an easily oxidizable green body containing rare earth NdFeB ultrafine powder is placed in the sintering environment for co-firing.
2. The method for reducing the oxygen content of sintered NdFeB magnets according to claim 1, characterized in that: The particle size D50 of the rare earth NdFeB ultrafine powder is less than 1.5 μm.
3. The method for reducing the oxygen content of sintered NdFeB magnets according to claim 1, characterized in that: The rare earth NdFeB ultrafine powder is collected during the jet milling process; Preferably, the total amount of rare earth in the rare earth NdFeB ultrafine powder is ≥50wt%.
4. The method for reducing the oxygen content of sintered NdFeB magnets according to any one of claims 1 to 3, characterized in that: The easily oxidizable green body contains 1wt‰ to 5wt‰ of antioxidant and 1wt‰ to 5wt‰ of lubricant.
5. The method for reducing the oxygen content of sintered NdFeB magnets according to claim 4, characterized in that: The easily oxidizable green body is prepared by the following preparation method: The rare earth NdFeB ultrafine powder, antioxidant and lubricant are mixed and pressed to obtain the easily oxidizable green compact.
6. The method for reducing the oxygen content of sintered NdFeB magnets according to claim 5, characterized in that: The mixing is carried out in a mixer, and the mixing time is 60 to 90 minutes.
7. The method for reducing the oxygen content of sintered NdFeB magnets according to claim 5, characterized in that: The compression molding is performed in an environment where the oxygen content is less than 20 ppm.
8. The method for reducing the oxygen content of sintered NdFeB magnets according to claim 1, characterized in that: During the sintering, the volume ratio of the easily oxidizable green body to the NdFeB magnet green body in the same sintering environment is 1:9 to 2:
3.
9. The method for reducing the oxygen content of sintered NdFeB magnets according to claim 8, characterized in that: During sintering, the easily oxidizable green compacts are dispersed and placed; Preferably, the easily oxidizable green body is placed at the edge of the sintering environment. And / or, the easily oxidizable green compact and the NdFeB magnet green compact are placed at intervals.
10. A neodymium iron boron magnet, characterized in that: The magnet is prepared by the method for reducing the oxygen content of sintered NdFeB magnets as described in any one of claims 1 to 9.
Citation Information
Patent Citations
Method for reducing oxygen content of sintered neodymium-iron-boron permanent magnet
CN111554499A